Analisis Faktor-Faktor Multipikasi Efektivitas Kepemimpinan Kristen di Era Digital - Glori Aaron Rumondor; Dean Justine Ticoalu; Manlian Ronald A. Simanjuntak (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
The digital transformation has redefined how Christian leaders fulfill their roles, shifting leadership from being solely grounded in physical presence to requiring adaptability in digital environments. This study explores the key factors that influence the multiplication of effective Christian leadership in the digital era, focusing on maintaining a balance between technological engagement and spiritual integrity. Using a qualitative approach based on literature review, the study identifies several crucial elements contributing to leadership effectiveness: strong digital communication skills, impactful online presence, structured online discipleship, and hybrid ministry models that integrate both virtual and in-person interactions. These factors help leaders reach wider audiences and foster community despite geographical barriers. However, the digital context also introduces new challenges, such as the risk of superficial spiritual relationships and the temptation to prioritize digital popularity over genuine spiritual growth. The findings highlight the need for Christian leaders to uphold their core values, authenticity, and moral responsibility in the face of technological advancement. By doing so, they can maintain trust, inspire their followers, and expand their ministry influence while navigating the complexities of a rapidly evolving digital landscape. This study concludes that the future of Christian leadership depends on leaders who are both digitally competent and spiritually grounded.